Readiness of Chemistry Teachers of Riau Province Viewed from Attitude Aspect in Applying 4C (Critical Thinking, Creative Thinking, Communication and Collaboration) - Saputri, Agustina Eka; Copriady, Jimmi; Erna, Maria (Journal of Educational Sciences, 2020)
This study aims to determine the readiness of chemistry teachers in applying 4C skills (critical thinking, creative thinking, communication and collaboration) in terms of attitude aspects. The 4C skills are needed to prepare students to compete in the era of globalization and teachers which are the main factors for students success in mastering 21st century learning. This research was a descriptive and inferential study involving as many as 115 high school chemistry teachers in Pekanbaru City and Pelalawan district. The instruments used a Likert scale questionnaire 5 consisting of demographics of respondents and 4 variables to measure the ability of the 4C. The results of the analysis showed that the readiness of chemistry teachers in Pekanbaru City and Pelalawan regencies in Riau Province was seen from the aspect of attitudes at a high level. Data were analyzed descriptively based on mean values ​​and standard deviations as well as independent t tests and one way anova to determine differences in the readiness of high school chemistry teachers based on gender, years of service and educational qualifications. Thus, there were significant differences in the readiness of chemistry teachers in high school levels based on educational qualifications